AUDIT ENERGI AWAL MELALUI PERHITUNGAN INTENSITAS KONSUMSI ENERGI (IKE) LISTRIK (STUDI KASUS PADA GEDUNG POLITEKNIK MUARA TEWEH) - Juli Chandra Teruna (Elektrika Borneo, 2019)
An audit of electricity is evaluation of the utilization of energy and identification savings opportunities electricity energy as well as recommendations an incrase in the efficiency  on  users of energy source and users energy in order to conservation energy. Energy audit review of the condition and operation of equipment that uses electricity energy as well as instruments related to energy efficiency. Based on the result of research, the effective extensive  Politektik  Muara  Teweh  building  is  615m2  with an average energy consumption is  2598 kWh  each  month  while the consumption of electricity energy index amounted to 4,224 kWh/m2 each  month  or  by  50,698 kWh/m2  each  year  with  energy  of  bulding  cost  amounted  to Rp. 902,47/kWh. Consumption of electricity energy of Politeknik Muara Teweh including very efficient criteria. This audit energy is expected to be identify opportunities for savings electricity energy consumption through energy audit detailed.